Sustentabilidade de Sistemas Agroflorestais (SAF) no semiárido cearense utilizando insumos locais - Ziegler, Henrique Ricardo Souza (2013)
For thousands of years, people have practiced different forms of agriculture, based mostly on the handling of materials available in their own land. Among these, we highlight the organic origin, that allow an improvement of soil quality and increased crop production. In this context, this dissertation presents a study of five years, from 2008 to 2012, of an Agroforestry System (AFS) for growing corn and beans intercropped with gliricidia and cashews, in conditions of northern coast of Ceará. The (AFS), had four treatments: Testimony (A), under normal conditions the AFS; Dung (B), with the addition of 116 grams of sheep dung in the pit of corn and beans at planting time; Bagana (C), with addition of 16 tons of carnauba straw on the soil as mulch; and Dung + Bagana (D), which is a combination of treatments B and C. In addition to the experimental treatments, 10 local farmers were interviewed to develop the treatment (T) Regional Testimony (local production system). Two analyzes were performed comparing this 5 treatments: Productivity of the system and its Economic analysis. It was concluded that the AFS assists in fixing agriculture, avoiding the opening of new areas for cultivation, having succeeded to higher production levels than the obtained by local itinerant cultivation. Regarding the productivity, was noticed an increasing pattern from treatment T (lower middle), through A, to the D, which has always had the highest average productivity besides showing greater resilience to the effects of drought. The T and A treatments were not economically viable, with negative indicators. Whereas the B, C and D treatments proved feasible economically and financially, with the best indicators in treatment D. For this set of analyzes, the proposed AFS, especially the treatment D, presents itself as the most advantageous for the exploitation of agriculture in studied conditions.